Genetic parameter estimates of chick quality, growth, and carcass characteristics in Japanese quail - NARINÇ, D; AYDEMIR, E (Journal of the Hellenic Veterinary Medical Society, 2022)
The aim of this study was to estimate the heritabilities of chick quality and growth traits and their genetic relationships with some slaughter traits. Chick quality was determined using both Tona and Pasgar score methods. All birds were slaughtered at 8 weeks of age to measure carcass yield (CY), and percentage of breast (BY), leg (LY), wing (WY), abdominal fat (AFY). Heritability estimates for chick quality scores of Tona and Pasgar were found 0.08, and 0.09, respectively. Heritability estimates for growth curve parameters and inflection point coordinates of the Gompertz model were low to moderate, with values ranging from 0.17 to 0.26. Low heritability estimates for CY, BY, LY, and WY were found 0.04, 0.14, 0.09, and 0.07, respectively. Genetic and phenotypic correlations between chick quality and BW-growth traits were determined low and statistically non-significant (P>0.05). Similarly, genetic and phenotypic relationships between chick quality and carcass yield, and between chick quality and percentages of carcass parts were found low and statistically non-significant (P>0.05). As a result, it is possible to say that applying multitrait selection, including chick quality, will not affect other yield characteristics positively or negatively. However, in virtue of the chick quality is a very low heritable trait, environmental improvement of chick quality trait may be considered rather than genetic improvement.